2018
DOI: 10.1176/appi.ajp.2017.17060693
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of DNA Methylation in Young People: Limited Evidence for an Association Between Victimization Stress and Epigenetic Variation in Blood

Abstract: Objective DNA methylation has been proposed as an epigenetic mechanism by which early-life experiences become “embedded” in the genome and alter transcriptional processes to compromise health. The authors sought to investigate whether early-life victimization stress is associated with genome-wide DNA methylation. Method The authors tested the hypothesis that victimization is associated with DNA methylation in the Environmental Risk (E-Risk) Longitudinal Study, a nationally representative 1994–1995 birth coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
107
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
3

Relationship

2
8

Authors

Journals

citations
Cited by 151 publications
(117 citation statements)
references
References 63 publications
6
107
2
2
Order By: Relevance
“…These results are consistent with at least one human longitudinal study (16) and multiple animal studies (21,22,24,25) in emphasizing the existence of sensitive periods (19,20) particularly occurring shortly after birth -when epigenetic programming is maximally dynamic in response to parental care disruptions and other environmental inputs. The lack of detectable sensitive periods in one recent study (32) may be due to focusing only on adversities occurring at or after 5 years of age. Interestingly, neither the accumulation nor recency of the adversity explained considerable variability in DNAm.…”
Section: Discussionmentioning
confidence: 92%
“…These results are consistent with at least one human longitudinal study (16) and multiple animal studies (21,22,24,25) in emphasizing the existence of sensitive periods (19,20) particularly occurring shortly after birth -when epigenetic programming is maximally dynamic in response to parental care disruptions and other environmental inputs. The lack of detectable sensitive periods in one recent study (32) may be due to focusing only on adversities occurring at or after 5 years of age. Interestingly, neither the accumulation nor recency of the adversity explained considerable variability in DNAm.…”
Section: Discussionmentioning
confidence: 92%
“…For example, much research is based on small, selected groups of children, with the assumption that results from these samples will generalise to the population at large ( where do we sample?) (Danese et al, ; Marzi et al, ). Furthermore, much research is based on complex measures of childhood trauma, with the assumption that different dimensions, such as threat, deprivation or unpredictability, have little relevance to the mechanisms involved or outcomes ( what do we measure as trauma?)…”
Section: Resultsmentioning
confidence: 99%
“…As substantially more of the PTSD cases reported smoking compared to controls, this suggested that we should control for smoking in the EWAS. A comparable approach was taken by Marzi and colleagues 50 . In their study of DNA methylation in relation to victimization stress in adolescents, they noted experiment-wide significant associations in 3 of the 4 AHRR CpGs associated with PTSD.…”
Section: Discussionmentioning
confidence: 96%